2006
DOI: 10.1111/j.1475-3588.2006.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

The Children And Parents Service (CAPS): A Multi‐Agency Early Intervention Initiative for Young Children and their Families

Abstract: Behaviour problems make up approximately 30–50% of all referrals to child and adolescent mental health services. Behavioural parent training is one of the most effective interventions for young children. However, those families most at risk of difficulties fail to access services. This paper outlines the Children And Parents Service (CAPS), a citywide multi‐agency, early intervention service to young children and their families. The intervention includes parent training groups, multi‐agency training and liaiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
5
0
3
Order By: Relevance
“…Taking into account the fact that recent studies suggest that those most likely to be in need are least likely to access services (White & Verduyn, 2006), Ward and Rose (2002) propose three levels of support as necessary to ensure that children do not ‘slip through the net’. The primary level is a universal preventative level that involves ‘community development’.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the fact that recent studies suggest that those most likely to be in need are least likely to access services (White & Verduyn, 2006), Ward and Rose (2002) propose three levels of support as necessary to ensure that children do not ‘slip through the net’. The primary level is a universal preventative level that involves ‘community development’.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence for the components of an effective community service to target children and families with early emerging behaviour problems. Both clinic‐based and community randomised controlled trials have shown that improving parenting skills via parent groups are effective in changing both parents’ and children’s behaviour (Gardner, Burton, & Klimes, 2006; Hutchings & Lane, 2006; Hutchings & Gardner et al, 2007; Kazdin, 1995; Scott et al, 2001; Webster‐Stratton, Reid, & Hammond, 2001; White, Agnew, & Verduyn, 2002; White & Verduyn, 2006). In addition to parenting groups, consultative working and training with nursery staff and teachers adds to the likely success of intervention programmes (Webster‐Stratton & Reid, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As alterações de comportamento, definidas como comportamentos reativos e desafiantes das regras sociais por parte dos adolescentes, no contexto familiar, escolar e na relação com os pares (não preenchendo a totalidade dos critérios para o diagnóstico de perturbação de comportamento e/ou de oposição) e as dificuldades de gestão das mesmas por parte dos pais surgem como um dos motivos de referenciação mais frequente (30 a 50%) de adolescentes para serviços de saúde mental (White & Verduyn, 2006) e para serviços de primeira linha ao nível dos cuidados de saúde primários (CSP) (CNCA, 2009). Com o patrocínio da Organização Mundial da Saúde, o último estudo "Health Behaviour in School-aged Children" realizado em Portugal e apresentado em 2011, mostra que 36.6% dos alunos referem ter sido vítimas de provocação uma vez nos últimos dois meses, enquanto 31.8% dos alunos admitem ter provocado outros pelo menos uma vez nos últimos dois meses (Matos et al, 2011).…”
Section: Introductionunclassified
“…Neste contexto, a intervenção poderá ser de dois tipos: mais focada no contexto da escola ou mais focada na família. O aconselhamento e o treino parental surgem como uma das intervenções mais efetivas, existindo contudo uma dificuldade de acesso às abordagens desta natureza pela sua escassez (Dretzke et al, 2009;White & Verduyn, 2006). Na literatura, estão disponíveis estudos de metanálise que evidenciam os efeitos benéficos de intervenções psicossociais com crianças e adolescentes com alterações de comportamento, mas não incluindo a família de forma sistemática.…”
Section: Introductionunclassified
See 1 more Smart Citation